STUDY OF MORPHOLOGY AND MORFOMETRY KINTAMANI DOG DUODENUM - Septiyatma, Andika Diko; Setiasih, Ni Luh Eka; Heryani, Luh Gde Sri Surya (Buletin Veteriner Udayana, 2020)
The kintamani dog is a native dog from Bali that has an attractive and a gorgeous appearance. The aim of this research was to know the morphology and morphometry of kintamani dog's duodenum. This study used five female kintamani dogs. The observation of histologic morphology used a binocular light microscope with 5x, 10x, and 20x magnification. The results showed that length of duodenum is 16.2 ± 1.3 cm, and the width of duodenum are 3.1 ± 0.1 cm. The duodenal histology structure is composed of four layers: tunica mucosa, submucosa, muscularis, and serosa. Tunica mucosa thickness: 1,364.584 ± 255.504 mm, tunica submucosa: 360.136 ± 188.283 mm, tunica muscularis: 689.178 ± 267.228 mm, tunica serosa: 25.888 ± 11.93 mm.